The Effect of Land Slope Level on Productivity of Pujon Agroforestry - Joko Triwanto; Amir Syarifuddin; Lala Aprilia (Universitas Muhammadiyah Malang, 2024)
The slope of the land can influence accessibility, water movement, and soil characteristics, thereby affecting the productivity of agroforestry plants. This study aims to analyze the effect of land slope on agroforestry productivity. The methods employed included field observations and questionnaires to collect data. A total of 100 farmers from various locations participated as respondents in this study. Regression analysis was conducted to determine and compare the influence of land slope on the productivity of agroforestry crops. The results of the analysis indicated that land slope does not significantly affect land productivity. The highest net income for farmers on slopes of 15-30% was from chili crops, amounting to Rp 76,987,600 per year with a B/C Ratio of 2.97, while the lowest was from cauliflower crops, with an income of Rp 31,586,800 per year and a B/C ratio of 1.74. The distribution of plant species across different slope levels was relatively uniform. Thus, the slope of the land does not have a significant effect on the success and productivity of the agroforestry system.